The Effect of Sediment Storage in Glaciated Catchments on Multimineral Detrital Geochronology: Deciphering Conflicting Zircon and Apatite U‐Pb Dates. Issue 1 (24th January 2023) - Jess, Scott; Enkelmann, Eva; Matthews, William
Abstract: Detrital geochronology and thermochronology are widely used to study erosion and the exhumation of rocks. In glaciated landscapes, these studies have shown exhumation to be highly heterogeneous; however, these studies have typically only applied apatite low‐temperature thermochronology, a mineral prone to mechanical and chemical breakdown, and a method with lower precision or data dispersion. As such, it is unclear if the detrital apatite signal represents derivation from the entire catchment. In this study, we present both zircon and apatite U‐Pb dates from a modern detrital sample of the Saco River, New Hampshire, USA. The river flows through a catchment that was highly modified during the last glacial maximum. The underlying geology is characterized by two contrasting groups from different eras; Palaeozoic metasediments and granites, and Mesozoic granitoids. Zircon U‐Pb dates are consistent with near‐uniform erosion of the catchment, encompassing both Proterozoic–Palaeozoic and Jurassic–Cretaceous grains consistent with the catchment's geology. However, detrital apatite U‐Pb dates are predominantly Palaeozoic. Detrital U‐Pb modeling shows that zircon grains are indeed derived from erosion of the entire catchment, while apatites likely originate from areas at high elevation. This stark contrast in ages likely indicates apatite's fragility. Dissolution resulting from acidic soils in the river's catchment is a likely cause, though mechanical breakdown during transport is also possible. As such, the detrital apatite signal appears to only record erosion from the modern fluvial system, while zircon represents a combination of uniform erosion during glaciation and the modern fluvial system. These findings imply the detrital apatite signal is prone to significant modification in areas of sediment storage and acidic soils with implications for sediment generation in other formerly glaciated landscapes worldwide. Plain Language Summary: We use river sands to study the origins of sediment and whether erosion across a river catchment is uniform. Should this be the case, dates from these detrital minerals should be consistent with the exposed bedrock of a river's catchment. However, the properties of minerals can vary, leading some to break down during river transport, while others remain unaffected. In this study we test if two commonly used minerals with contrasting physical and chemical properties, zircon and apatite, produce dates consistent with the bedrock geology of the Saco River, New Hampshire, USA. The catchment of the SR contains two major bedrock groups that differ in age. Two‐thirds are made up of 200–150 million‐year‐old granites, while the remaining third consists of metamorphic rocks and granites older than 300 million years. We found that zircon dates from river sands are highly consistent with the geology of the river's catchment. In contrast, apatite dates are highly inconsistent, and notably lack dates between 200 and 150 million years old. Computer modeling shows that zircon is likely sourced from all areas of the catchment, while apatite is only derived from rocks exposed at high elevations. Collectively, these results imply a large portion of apatite grains have been broken up during transport or dissolved by acidic soils present in the low elevation regions of the catchment. This work is important for future studies dating river sands and has implications for how we study sediment in formerly glaciated areas. Key Points: Detrital U‐Pb dates for zircon and apatite differ unexpectedly in the previously glaciated Saco River, USA Modeling shows zircon is consistent with uniform erosion, while apatite represents elevation dependant erosion Results suggest acidic soils and sediment transport have removed large portions of apatite from detrital population